Hole Transfer and the Resulting DNA Damage - Chryssostomos Chatgilialoglu; Andrea Peluso (Biomolecules)
In this review, we focus on the one-electron oxidation of DNA, which is a multipart event controlled by several competing factors. We will discuss the oxidation free energies of the four nucleobases and the electron detachment from DNA, influenced by specific interactions like hydrogen bonding and stacking interactions with neighboring sites in the double strand. The formation of a radical cation (hole) which can migrate through DNA (hole transport), depending on the sequence-specific effects and the allocation of the final oxidative damage, is also addressed. Particular attention is given to the one-electron oxidation of ds-ODN containing G:C pairs, including the complex mechanism of the deprotonation vs. hydration steps of a G:C•+ pair, as well as to the modes of formation of the two guanyl radical tautomers after deprotonation. Among the reactive oxygen species (ROS) generated in aerobic organisms by cellular metabolisms, several oxidants react with DNA. The mechanism of stable product formation and their use as biomarkers of guanine oxidation in DNA damage are also addressed.